[PP.29.14] SYMPATHETIC ACTIVITY IS DECREASED IN PATIENTS WITH POLYCYTHEMIA VERA AS COMPARED WITH PATIENTS WITH ESSENTIAL HYPERTENSION. (September 2017) - Lewandowski, J.; Sinski, M.; Sikorska, A.; Kaszuba, A.; Wojcicki, J.; Prejbisz, A.; Florczak, E.; Kabat, M.; Januszewicz, M.; Gaciong, Z.; Wiecek, A.; Windyga, J.; et al.
Abstract : Objective: Polycythemia vera (PV) is commonly considered to be a secondary form of hypertension. Data on pathogenetic mechanisms of hypertension in this group of patients is limited. The aim of the study is to present a selected clinical, neural and hemodynamic characteristics of hypertension in subjects with PV. Design and method: From the group of 22 patients diagnosed with PV in our ongoing study, we included 12 consecutive patients (7F) with PV diagnosed (according to the WHO criteria), who underwent successful muscle sympathetic nervous activity (MSNA) measurements and 16 subjects with essential hypertension (EH) matched for age, gender, body mass index, blood pressure levels and number of medication (p > 0.05). All patients underwent detailed clinical investigation which included among others: office blood pressure (BP), ambulatory BP monitoring (ABPM) and MSNA measurement. Results: Patients with PV and with EH had similar systolic and diastolic BP values both in office and ambulatory blood pressure measurements. There were no differences in office HR between groups, however in EH patients had significantly higher HR in ABPM during 24 h, day- and night-time (table 1.). Patients with PV were characterized by lower MSNA/min and MSNA /100 heart beats than EH patients (30, 7 ± 8, 7/min vs 38, 7 ± 5, 4/min, p = 0.007 and 51, 8 ± 11, 0/100 heart beats vs 61, 1 ± 11, 3/100 heart beats, p = 0.04, respectively). There was a positive correlation between MSNA/min and night HR in PV group (r = 0.617, p < 0.05). Figure. No caption available. Conclusions: Patients with PV were characterized by lower indices of sympathetic nervous system activity expressed as MSNA and HR.